2021
DOI: 10.1051/bioconf/20213700080
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of government support measures for reclamation as an incentive for the development of the agricultural industry: Experience of the Republic of Tatarstan

Abstract: The article discusses the issue of government support for reclamation activities in the context of new challenges of the economic environment. The relevance of the issue is due to the need for intensive development of the agricultural sector caused by globalization processes, which have created fierce competition, both in the international and domestic food markets. Sustainable production of agricultural products on irrigated lands is one of the main indicators of the efficiency of the agro-industrial complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Studies in Kazakhstan's neighboring countries have found that vegetation on dumps naturally regenerates in a pattern similar to primary succession, which is the process of plant colonization on a previously unvegetated area. These studies provide valuable insights for post-mined reclamation in Kazakhstan (Shandala et al 2016;Belov et al 2020;Korniyenko et al 2020;Khismatullin et al 2021;Klimova et al 2021;Tchoroev 2021;Treschevskaya et al 2021;Edelev et al 2022;Henyk et al 2022;Chaplygina et al 2023).…”
Section: Introductionmentioning
confidence: 98%
“…Studies in Kazakhstan's neighboring countries have found that vegetation on dumps naturally regenerates in a pattern similar to primary succession, which is the process of plant colonization on a previously unvegetated area. These studies provide valuable insights for post-mined reclamation in Kazakhstan (Shandala et al 2016;Belov et al 2020;Korniyenko et al 2020;Khismatullin et al 2021;Klimova et al 2021;Tchoroev 2021;Treschevskaya et al 2021;Edelev et al 2022;Henyk et al 2022;Chaplygina et al 2023).…”
Section: Introductionmentioning
confidence: 98%
“…The carried out erosion control measures must be systematic and take into account the specific natural and economic conditions of each economic entity [13][14][15]. In order to ensure that erosion control measures are carried out effectively, it is necessary to:…”
Section: Introductionmentioning
confidence: 99%
“…В результате банкротства сельскохозяйственных организаций, крестьянских (фермерских) хозяйств и по другим причинам увеличиваются площади, выведенных из оборота земельных угодий. По данным Министерства сельского хозяйства РФ площади таких земель в 2020 году составили 44,5 млн га, из них сельскохозяйственные угодья -33 млн га [19,20]. Проблема усложняется и тем, что слабой является и материально-техническая база организаций службы мелиорации, которые обеспечены необходимой техникой только на уровне 50% от потребности.…”
unclassified